IConnect CKD – virtual medical consulting: A web‐based chronic kidney disease, hypertension and diabetes integrated care program. Issue 7 (24th July 2018) - Katz, Ivor J; Pirabhahar, Saiyini; Williamson, Paula; Raghunath, Vishwas; Brennan, Frank; O'Sullivan, Anthony; Youssef, George; Lane, Cathie; Jacobson, Gary; Feldman, Peter; Kelly, John
Abstract: Aims: Chronic kidney disease patients overwhelm specialist services and can potentially be managed in the primary care (PC). Opportunistic screening of high risk (HR) patients and follow‐up in PC is the most sustainable model of care. A 'virtual consultation' (VC) model instead of traditional face to face (F2F) consultations was used, aiming to assess efficacy and safety of the model. Methods: Seventy patients were recruited from PC sites and hospital clinics and followed for 1 year. The HR patients (eGFR < 30 mL/min/1.73m 2 +/− albuminuria >30 mg/mmol/L) were randomized to either VC or F2F. Patients were monitored in 6 monthly follow‐up cycles by a Clinical Nurse Specialist. The specialist team provided virtual or clinical support and included a Nephrologist, Endocrinologist, Cardiologist and Renal 'Palliative' Supportive Care. Results: Sixty one (87%) patients were virtually tracked or consulted with 14 (23%) being HR. At 12 months, there was no difference in outcomes between VC and F2F patients. All patients were successfully monitored. General practitioners reported a high level of satisfaction and supported the model, but found software integration challenging. Patients found the system attractive and felt well managed. Specialist consults occurred within a week, and if a second specialist opinion was required, it took another 2 weeks. Conclusions: The programme demonstrated safe, expedited and efficient follow up with a clinical and web based programme. Support from the general practitioners and patients was encouraging, despite logistical issues. Ongoing evaluation of VC services will continue and feasibility to larger networks and more chronic diseases remains the long term goal. Summary at a Glance: This Virtual Medical Consulting program demonstrated a safe, expedited and efficient follow up with a clinical and web based program for CKD patients care, despite the need for long term validation.